Museum studies for a post-pandemic world : mentoring, collaborations, and interactive knowledge transfer in times of transformation - Cempellin, Leda, 1973-; Crawford, Pat (Patricia) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Museum Studies for a Post-Pandemic World demonstrates that digital literacy, creativity, and resilience, as the COVID-19 pandemic has so vividly illustrated, are now vital components of the classroom and of the curator's toolbox. Museum studies students are increasingly asked to engage with new team dynamics and collaborative models, often relocated to the virtual world. Authored by academics, cultural heritage partners, students, and alumni, the chapters in this volume move beyond a consideration of the impact of digitization to envision new strategies and pedagogies for fuller, more sustainable approaches to cultural literacy, exhibition, and visitor engagement. International case studies present models of collaborative practices between teams of diverse sizes and professional backgrounds. The volume demonstrates that the COVID-19 pandemic has forced the use of a variety of pedagogically and culturally significant hybrid and virtual models that provide innovative learning modalities to meet the needs of future generations of digital native patrons. The book offers meaningful strategies that will help academic and cultural heritage institutions engaged in museum studies to survive--and even thrive--in the face of future disasters by expanding program accessibility beyond the physical confines of their buildings. Museum Studies for a Post-Pandemic World will be of interest to students and researchers engaged in the study of museums, the arts, cultural management, and education. It should also be of interest to museum practitioners around the world"--
Why We Gather : Connecting and Sharing -- Pivoting our Pedagogical Skills to Affect Change -- Creative Tensions : Bridging the Academic-Workforce Gap -- The Impact of Space and Architecture in Transforming Museum Studies.
Collection of essays by Chiara O'Reilly and 38 others.
Keywords: Museum studies -- Web-based instruction; Museum techniques -- Technological innovations; Museum exhibits -- Technological innovations; Virtual museum exhibits; Cultural property -- Technological innovations; LANGUAGE ARTS & DISCIPLINES / Library & Information Science